2019
DOI: 10.1016/j.apenergy.2018.10.046
|View full text |Cite
|
Sign up to set email alerts
|

Economic viability of multiple algal biorefining pathways and the impact of public policies

Abstract: This study makes a holistic comparison between multiple algal biofuel pathways and examines the impact of co-products and methods assumptions on the economic viability of algal systems. Engineering process models for multiple production pathways were evaluated using techno-economic analysis (TEA). These pathways included baseline hydrothermal liquefaction (HTL), protein extraction with HTL, fractionation into high-value chemicals and fuels, and a small-scale first-of-a-kind plant coupled with a wastewater trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…Direct and catalytic thermal pyrolysis of algae, especially microalgae for biofuels (bio-oil, biodiesel, syngas, etc. ) and biochar production is a major research focus in 2019 (Anto et al 2019;Ashokkumar et al 2019;Cruce and Quinn 2019). Algae biofuels are renewable and represent a promising alternative to fossil fuels; its production could mitigate the issue of the excessive use of fossil fuels (Anto et al 2019).…”
Section: Biochar Productionmentioning
confidence: 99%
“…Direct and catalytic thermal pyrolysis of algae, especially microalgae for biofuels (bio-oil, biodiesel, syngas, etc. ) and biochar production is a major research focus in 2019 (Anto et al 2019;Ashokkumar et al 2019;Cruce and Quinn 2019). Algae biofuels are renewable and represent a promising alternative to fossil fuels; its production could mitigate the issue of the excessive use of fossil fuels (Anto et al 2019).…”
Section: Biochar Productionmentioning
confidence: 99%
“…Biofuels derived from microalgae are still not commercially viable because their costs are higher than gasoline (Cruce and Quinn, 2019). Thus, the sustainability of projects that aim to cultivate microalgae for the production of biofuels and other bioproducts is generally evaluated using technoeconomic analysis and/or life cycle assessment (LCA) (Grierson et al, 2013).…”
Section: Economic and Environmental Analyses Associated With Microalgae Cultivationmentioning
confidence: 99%
“…They showed that for hydrothermal liquefaction, protein extraction, fractionation and novel pathways, the results were comparable to other biofuel studies, at $5.37, $4.44, $4.31 and $11.13 gge −1 respectively. They also showed that mixing the algal biorefinery with the treatment of wastewater surprisingly provided only minor benefits to system economics [47].…”
Section: The Use Of the Algae In Agricultural Production-potential Anmentioning
confidence: 99%